Legal Protection for Child Narcotics Prisoners at the Class I Special Development Institution for Children in Medan (An Islamic Law Perspective and Law No. 11 of 2012 on the Juvenile Criminal Justice System) - Nasution, Muhammad Zulfadli; Pagar, Pagar; Siregar, Ramadhan Syahmedi (UNIVERSITAS PAKUAN, 2025)
This study aims to explain the Legal Protection for Child Prisoners of Narcotics at the Class I Special Development Institution for Children in Medan based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The type of research used by the author is field research with a qualitative descriptive method. It employs a socio-legal approach and a statute approach, while the types of data used consist of primary and secondary data. The problem in this study is that Article 98 paragraph 1 of the Compilation of Islamic Law states that the age limit for a child who is able to stand independently or is considered an adult is 21 years, provided that the child does not have physical or mental disabilities and has never been married. The results of this study indicate that the Legal Protection for Child Prisoners of Narcotics at the Class I Special Development Institution for Children in Medan based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System is, in Islamic law, known as Maqāsid Al-Syarī’ah, which consists of two words: Maqāsid, meaning objectives and purposes, and Al-Syarī’ah, meaning the establishment of Allah’s law, which serves as a guide for humans to achieve happiness in this world and in the hereafter.